The Impact of Bektashi Penetration on the Ottoman Empire - Meirison Meirison; Testru Hendra; Efendi Efendi; Ayu Rustriana Rusli (AL-TAHRIR, 2022)
This article aims to explain the role of Bektashi Sufism. It was practiced for centuries in the Ottoman Empire and is considered a branch of the Ja’fari school of Shia. The Imams of the Ahl al-Bayt (Shia) had developed and adapted to the style of Sufism that surrounded them. So far, the Shiites have conflicted with the Sunnis. Social penetration was successful, and many Bektashi followers declared that they had converted to Islam, like Christians and Jews. The problem of the sect adhered to by Bektashi is still being debated. Who is the Bektashi group? Are these groups Shiites or Sunnis? By analyzing and applying the theory of interpersonal relations and openness by the Bektashi group, which ruled out the Ja’fari Fiqh thinking to abolish differences in Sufism, Bektashi penetrated Sunni bodies. The writers used a literature study. It employed a descriptive and qualitative analysis to conduct a historical discussion of this unique Bektashi school of thought. The teachings of Bektashi affected the spirit of jihad of the Ottoman Turkish troops, who came from Christian prisoners of war. They won many victories with the guidance and support of the Bektashi group. Bektashi’s teachings are also compatible with religious tolerance, openness, and moderation inspired by various styles of thought and philosophy.